Kinematics analysis on the vaulting-horse movement -round -off with 1/2 Twist to forward handspring and salto stretched with twist 5/2 performed by Li Xiao-Peng - Yao, X.-W.; Ji, Z.-Q.; Xu, Y.-Y.; Li, J. (Journal of Beijing Sport University, 2005)
Based on the kinematics analysis, this research explores the kinematics principles and the technical charateristics of the movement-round-off with 1/2 twist to forward handspring and salto stretched with twist 5/2 performed by Li Xiao-peng, a world horse-vaulting champion from China, and provides technical references and theoretical foundation for the further development of Chinese athletes in this field.